REMOVAL OF MICROPLASTICS BY ELECTROCOAGULATION - PILCO-NUÑEZ, ALEX (2024)
WITH THE GRADUAL INCREASE OF MICROPLASTICS IN WATER BODIES, IT IS ESSENTIAL TO UNDERSTAND THE CURRENT TREATMENT PROCESSES FOR THEIR REMOVAL. THIS STUDY AIMS TO INVESTIGATE THE REMOVAL OF MICROPLASTICS IN SYNTHETIC SOLUTION BY ELECTROCOAGULATION (EC). THE EFFECTS OF ELECTRODE TYPE, CONTACT TIME (MIN), AGITATION SPEED (RPM) AND CURRENT DENSITY (A/M2) WERE EVALUATED USING A FRACTIONAL FACTORIAL DESIGN. THE RESULTS SHOWED THAT THE ALUMINUM ANODE ACHIEVED A HIGHER REMOVAL OF MICROPLASTICS THAN THE IRON ANODE, REACHING 98.04% REMOVAL WITH THE ALUMINUM OPERATIONAL CONFIGURATION WITHIN 15 MIN AT 70 RPM AND A CURRENT DENSITY OF 20 A/M2. A HIGH CORRELATION BETWEEN THE PREDICTED AND OBSERVED REMOVAL WAS EVIDENCED, WITH VALUES OF R2= 0.99 AND ADJUSTED R2= 0.98, INDICATING A GOOD AGREEMENT BETWEEN THE MODEL AND THE EXPERIMENTAL DATA, CONFIRMING THE VALIDITY AND FEASIBILITY OF THE ADOPTED LINEAR MODEL. THIS STUDY DEMONSTRATES THAT THE ELECTROCOAGULATION PROCESS HAS A GREAT POTENTIAL FOR THE REMOVAL OF MICROPLASTICS. © 2024 POLSKA AKADEMIA NAUK. ALL RIGHTS RESERVED.